Tomada antes de ir al Pará (Brasil) mamá y Raúl - 1932 - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1932)
SPANISH: Señor y señora Morey con cuatro de sus hijos posando para ser fotografiados antes de ir a Pará (Brasil)
ENGLISH: Mr. and Mrs. Morey with four of their children posing to be photographed before going to Pará (Brazil).

SPANISH: Señor y señora Morey con cuatro de sus hijos posando para ser fotografiados antes de ir a Pará (Brasil)
ENGLISH: Mr. and Mrs. Morey with four of their children posing to be photographed before going to Pará (Brazil).
Taken before going to Pará (Brazil) mom and Raul - 1932
Keywords: Iquitos (Perú)|~|Upper class families|~|Photograph albums|~|Albúm de la Familia "Morey"|~|Iquitos (Perú)|~|familia de la clase alta|~|album de fotografías